2016
DOI: 10.1002/jbio.201600221
|View full text |Cite
|
Sign up to set email alerts
|

A useful way to develop effective in vivo skin optical clearing agents

Abstract: Skin optical clearing has shown tremendous potential in improving various optical imaging performances, but there is some certain blindness in screening out high-efficiency in vivo optical clearing methods. In this work, three optical clearing agents: sucrose (Suc), fructose (Fruc) and PEG-400 (PEG), and two chemical penetration enhancers: propylene glycol (PG) and thiazone (Thiaz) were used. PEG was firstly mixed with the two penetration enhancers, respectively, and then mixed with Fruc and Suc, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…Diabetes can accelerate inflammation of wound caused by the surgery, which may affect the vascular function. 42 Fortunately, in vivo skin optical clearing method developed recently, 41 as a low-cost and convenient method, provides a good way for studying skin microvascular hemodynamics under pathological conditions. Additionally, under the consistent experimental condition, we found that arteriovenous blood flow and blood oxygen saturation almost kept unchanged before and after injection of saline.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Diabetes can accelerate inflammation of wound caused by the surgery, which may affect the vascular function. 42 Fortunately, in vivo skin optical clearing method developed recently, 41 as a low-cost and convenient method, provides a good way for studying skin microvascular hemodynamics under pathological conditions. Additionally, under the consistent experimental condition, we found that arteriovenous blood flow and blood oxygen saturation almost kept unchanged before and after injection of saline.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used the in vivo dorsal skin optical clearing method 41 to enhance the imaging qualities of LSCI and HSI. The dorsal skin optical clearing agent (DSOCA) was a mixture of PEG, thiazone, and sucrose [67.1% (wt./wt.)].…”
Section: In Vivo Skin Optical Clearing Methodsmentioning
confidence: 99%
See 3 more Smart Citations